The Oxford Handbook of the Economics of Gambling 2013
DOI: 10.1093/oxfordhb/9780199797912.013.0033
|View full text |Cite
|
Sign up to set email alerts
|

The Economics Of Lotteries: A Survey Of The Literature

Abstract: This chapter surveys the literature on the economics of lotteries and is organized around two central themes. The first section examines the microeconomic aspects of lotteries, including consumer decision-making under uncertainty, price and income elasticities of demand for lottery tickets, cross-price elasticities of lottery tickets to each other and to other gambling products, consumer rationality and gambling, and the efficiency of lottery markets. The second section covers topics related to public finance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 129 publications
0
22
0
Order By: Relevance
“…The literature consistently finds income elasticities of less than one for state lotteries as a whole, with variation in income elasticity across types of lottery games, as discussed in the lottery literature surveys by Grote and Matheson () and Perez and Humphreys (). That is, people in geographical areas with lower income spend a relatively greater percentage of their income on lottery products, resulting in state lotteries being a regressive source of state revenue.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The literature consistently finds income elasticities of less than one for state lotteries as a whole, with variation in income elasticity across types of lottery games, as discussed in the lottery literature surveys by Grote and Matheson () and Perez and Humphreys (). That is, people in geographical areas with lower income spend a relatively greater percentage of their income on lottery products, resulting in state lotteries being a regressive source of state revenue.…”
Section: Introductionmentioning
confidence: 79%
“…The literature consistently finds income elasticities of less than one for state lotteries as a whole, with variation in income elasticity across types of lottery games, as discussed in the lottery literature surveys by Grote and Matheson (2013) 1. U.S. Census Bureau.…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, Forrest et al (2004) found that although scratch cards substituted for the National Lottery, they did not cannibalize the Thunderball lottery game. Hence, lottery providers design their product range carefully to maintain acceptable levels of substitution, while increasing overall sales and maximizing related tax revenue (see also Grote & Matheson, 2013;Gulley & Scott, 1993).…”
Section: Lotteriesmentioning
confidence: 99%
“…Despite the relevance of socio‐demographic variables, most of the literature on the drivers of gambling demand focuses on the role of economic conditions, generally measured through income, and reveals that gambling consumption tends to be irregularly distributed across the population, with more disadvantaged groups spending larger shares of their income on gambling consumption (see Grote and Matheson for a review). Most of the international literature on the role of income on gambling demand uses, as a starting point, micro data derived from household surveys (Borg and Mason ; Clotfelter and Cook ; Kitchen and Powells ; Scott and Garen ; Beckert and Lutter ).…”
Section: The Determinants Of Gambling Demand: a Literature Reviewmentioning
confidence: 99%